Analysis of Non-Linear Static Procedure Based on Fema 356 to Evaluate Structural Performance in the Alton Apartment Building - Hastria Iqbal Pratama (Publikasi Indonesia, 2024)
Alton Apartment is a high-rise residential building. The city of Semarang, within a radius of 500 km, has a fault range with a strength of up to 8.3 magnitude. The purpose of this study is to calculate the performance level of the structure, find out the nonlinear static procedure conditions and whether the analysis results can be used, calculate the value of ductility R, check the boundaries between levels, check the influence of P-delta, adjust horizontal irregularities, and check the vertical irregularity conditions. This study uses the FEMA 356 method. New regulations are used in the analysis, such as peak acceleration maps and response spectra from PuSGeN in 2021, deaggregation maps of Indonesian earthquake hazards for planning and evaluation of earthquake-resistant infrastructure from the Director General of Cipta Karya in 2022, and earthquake resilience planning procedures for building and non-building structures from SNI 1726-2019. The result of the structure performance of the drift value is below 1% for the life safety (LS) performance level on the 250-year earthquake map, and the result of the drift value is below 2% for the collapse prevention (CP) performance level on the 100-year earthquake map. The results of the FEMA 356 condition one analysis show that the strength ratio (μstrength) value of less than μmax has been met for 250-year and 1000-year earthquake maps with a review of the x and y directions of the earthquake. The value of the R ductility in 250-year and 1000-year earthquakes is above seven according to the earthquake force holding system of special reinforced concrete sliding walls.